Ekspo Potensi Budaya Desa Bersaudara sebagai Upaya Peningkatan Modal Sosial dalam Program Sister Village - Kanthi Pamungkas Sari; Priyo; Ahwy Oktradiksa; Agus Setiawan (Jurnal SOLMA, 2021)
"The Culture of Sister Village Potential Expo" is one of the empowering activities that can increase the role of social capital as expected. In this activity, they involve representatives from all elements of society so that they can interact and collaborate directly. So far, natural disaster mitigation has been more focused on developing human capital than social capital. Social capital provides positive benefits to disaster mitigation. The method used in the activity is the Participatory Rural Appraisal (PRA) method and demonstrations. The result of community service is that every element of society is involved and builds closer interaction and realizes that they are part of the sister Village and have an agreement to carry out activities together according to their respective potential. All of the activities expected to increase the role of social capital in mitigating the eruption of Mount Merapi that can erupt at any time